Assessing Death Anxiety and its Correlates among Community Dwelling Elderly - Dr. Aaqib Shahzad Alvi; Dr. Maliha Gull Tarar; Dr. Ibad Ullah Sajid (Journal of Management Practices, Humanities and Social Sciences, 2022)
This descriptive study was designed to appraise the prevalence of death anxiety and its correlates among older adult. It was conducted on 150 elderly residents of the district Sargodha, who were chosen through multistage sampling. Interview Schedule, Death Anxiety Scale-15, and Coping Style Scale were used as instruments. The findings of the study indicated a pervasive prevalence of death anxiety among elderly. The majority of elderly reported moderate level of death anxiety and slightly less than one forth revealed lower level of death anxiety. The results of T-test analysis showed no variation gender wise and community wise on death anxiety. According to the research findings, both elderly men and women experienced the same level of death anxiety. However, illiterate elderly exhibited more death anxiety as compared to literate elderly. The findings regarding the factors associated with death anxiety indicates that fear of being aged, fear of loneliness, worry about leaving loved ones behind, fear of being destroyed and decaying of dead body after death, lack of religiosity, lower self esteem and poor physical conditions were the correlated factors that caused death anxiety among elderly. Moreover, chi square results revealed that age, qualification, family structure, number of family members (family size) and marital status had significant association with the level of death anxiety. In case of coping, the elderly are more prone to adopt emotion focused coping rather problem solving coping. To alleviate death anxiety in older adults, it is necessary to manage the contributing factors.